Mechanism characterization of bacterial inactivation of atmospheric air plasma gas and activated water using bioluminescence technology. (May 2019) - Suwal, Shyam; Coronel-Aguilera, Claudia P.; Auer, Jameson; Applegate, Bruce; Garner, Allen L.; Huang, Jen-Yi
Abstract: We assessed the efficacy of bacterial inactivation using a dielectric barrier discharge in three different plasma setups: plasma gas (PG), and direct and indirect plasma activated water (PAW), where deionized water was placed either between or away from the electrodes, respectively. We used bioluminescent Escherichia coli K12 lux as a model bacteria in a biosensor format to study the inactivation kinetics and mechanism of action of produced PG and PAW. The results showed that uninterrupted application of PG decreased bioluminescence rapidly by 1-log within the first minute and 3.6-log after 10 min of treatment. Exposing the bacterial culture with a sublethal dose of PAW (1 mL) rapidly decreased the bioluminescence; however, luminescence slowly recovered after exposure. Subsequent treatment with PAW decreased the bioluminescence to a lesser extent. In addition, direct PAW induced a greater decrease in bioluminescence compared to indirect treatments for both single and multiple exposures. In contrast to the PG, PAW treatments induced a lower bactericidal effect with 0.11 to 0.22-log reduction for indirect PAW and 0.2 to 0.32-log for direct PAW. Our results also indicate that antimicrobial activity of PAW decreased slowly within 20 min of its preparation. The rapid decrease in bioluminescence followed by a partial recovery in a repeatable pattern suggests an incomplete inactivation, and that the reducing power of the cell helps them to survive. Moreover, the complete and partial oxidation of NADH solutions in vitro by PG and PAW, respectively, strongly suggest that the lux fluorophore FMNH2 and other reducing cofactors could be the target of such treatment before other cell components. This hypothesis was supported by the tendency to recover luminescence by potentially replenishing the pool of FMNH2 after plasma treatment. It is also important to consider that the reducing power of the cell (NADH, NADPH, and FMNH2 ) is crucial for cell viability mostly due to reducing potential for critical metabolic reactions. Therefore, in situ bioluminescence monitoring technology can potentially serve as a unique approach to elucidate the mechanism of bacteria inactivation in real time. Industrial relevance: The present study developed three dielectric barrier discharge (DBD) plasma setups to produce plasma gas and plasma activated water, which can disinfect both food products and their contact surfaces regardless of geometry. Our in situ bioluminescent technology elucidated bacterial inactivation mechanisms of plasma treatments, which may potentially suggest sufficient exposures to plasma resulting in safe food products without deteriorating their quality. The results will help food manufacturers apply new plasma-based disinfection methods with appropriate treatments. Highlights: Three disinfection methods were developed based on atmospheric air DBD plasma. Bacterial inactivation kinetics was studied using in situ bioluminescence. Plasma gas treatment induced greater inactivation than plasma activated water. Oxidation of NADH suggests loss of membrane potential resulting in cell death.